Pencegahan Penyalahgunaan Narkoba Perspektif Al-Qur’an (Kajian Tafsir Maudhu’i) - Budi Suhartawan; Muizzatul Hasanah; Ahmad Yuda Saputra; Kardana Tri Pamungkas; Yanuar Agung Nugroho (Jurnal test, 2023)
Drug abuse is a very heartbreaking and worrying problem and humanitarian issue. Drugs have infected all ages, from the lower class to the upper class, from children to the elderly, and from the uneducated to the educated, and even the victims continue to fall. This paper aims to reveal the Qur'anic efforts and find alternative solutions that will be able to reduce the rate of circulation and find ways to prevent drug abuse in the Qur'an. This paper, including the type of library research, uses a thematic approach (Tafsir Maudu'i). A method that directs the view of a particular theme and then seeks the view of the Qur'an on that theme by collecting, understanding, and analyzing verses that talk about the theme under study. The research results and findings from this study, among others, are: first, strengthening the foundation of religion; second, fostering the Qur'anic generation; third, growing noble character; fourth, providing advice in a civilized manner; fifth, calling on goodness and preventing evil; sixth, praying that all matters will be expanded; seventh, continuously in obedience; and eighth, hastening to give advice about religion. Furthermore, this research is still far from perfect. Further research is needed with a more varied and comprehensive approach. So that the prevention of drug abuse can be more controlled.